Analisis Pernikahan Usia Dini di Kabupaten Bengkulu Tengah Tahun 2017 - Bintang Agustina Pratiwi; Wulan Angraini; Padila Padila; Nopiawati Nopiawati; Yandrizal Yandrizal (Jurnal Kesmas Asclepius, 2019)
The purpose of this study was to determine the cause of the incidence of early pregnancy recording in Bengkulu Tengah Regency. This study used a qualitative approach by revealing informants as many as 7 people using Purposive Sampling techniques in Central Bengkulu District. The latest information obtained is analyzed. Informants married early because there were no other activities after graduating from school, not understood from getting married, wanting to have a mate, not being a parent, there was encouragement from parents. Public media is used as a communication tool, to determine the date of dating. Environmental factors are the reason for informants to marry early in the morning, assuming marriage at an early age is normal. Lack of attention and sensitivity of parents to the problems being experienced by children due to busy working on plantations. The desire of oneself is also a factor of choice for informants to get married at an early age. The relationship between the KUA, the Health Office, the Education Office to provide assistance to the families of prospective teenagers and adolescents. In addition, the need for activeness from community leaders in controlling adolescents in the village. Keywords: Early Marriage, Media, Knowledge, Environment, Parents